Orfeo como autor mítico en los manuales hispanos de literatura griega: el lento derribo de un tópico historiográfico. - García Jurado, Francisco (Myrtia, 2017)
The main aim of this work is to seek the reasons of Orpheus' appearance as a mythical poet in the European and Spanish handbooks of Greek literature during the 19TH century. These reasons are looked for in two principal sources such as J.A. Fabricius' Bibliotheca Graeca (1790) that provides the contents linked to the poet's figure and the works attributed to him, as well as the new history of Greek literature (1831) by F.A. Wolf, where Orpheus is given the preferential place in the pre- Homeric stage of literature. Gradually, Orpheus as a mythical poet gives up his place to the "Orphic poets". That fact implies the dissemination of the orphic works in later stages of Greek literature.